Pediatric Vital Sign Distribution Derived From a Multi-Centered Emergency Department Database - Sepanski, Robert J.; Godambe, Sandip A.; Zaritsky, Arno L. (Frontiers in Pediatrics, 2018)
Background We hypothesized that current vital sign thresholds used in pediatric emergency department (ED) screening tools do not reflect observed vital signs in this population. We analyzed a large multi-centered database to develop heart rate (HR) and respiratory rate centile rankings and z-scores that could be incorporated into electronic health record ED screening tools and we compared our derived centiles to previously published centiles and Pediatric Advanced Life Support (PALS) vital sign thresholds. Methods Initial HR and respiratory rate data entered into the Cerner™ electronic health record at 169 participating hospitals’ ED over 5 years (2009 through 2013) as part of routine care were analyzed. Analysis was restricted to non-admitted children (0 to <18 years). Centile curves and z-scores were developed using generalized additive models for location, scale, and shape. A split-sample validation using two-thirds of the sample was compared with the remaining one-third. Centile values were compared with results from previous studies and guidelines. Results HR and RR centiles and z-scores were determined from 1.2 million records. Empirical 95th centiles for HR and respiratory rate were higher than previously published results and both deviated from PALS guideline recommendations. Conclusion Heart and respiratory rate centiles derived from a large real-world non-hospitalized ED pediatric population can inform the modification of electronic and paper-based screening tools to stratify children by the degree of deviation from normal for age rather than dichotomizing children into groups having “normal” versus “abnormal” vital signs. Furthermore, these centiles also may be useful in paper-based screening tools and bedside alarm limits for children in areas other than the ED and may establish improved alarm limits for bedside monitors.